The Effectiveness of Using AI in Improving Students' Understanding of Flat Building Materials for Grade V Elementary School - Ronny Mugara; Enjang Yusup Ali; Wita Sari (Universitas Pendidikan Ganesha, 2025)
The use of Artificial Intelligence (AI) in mathematics learning at the elementary school level is increasingly developing; however, its effectiveness in improving fifth-grade students’ conceptual understanding of plane geometry has not been widely proven empirically. In addition, the teaching of plane geometry still tends to be teacher-centered and lacks the integration of interactive technology, resulting in suboptimal conceptual understanding among students. This study aims to analyze the effectiveness of AI-based learning in improving students’ understanding of plane geometry concepts in Grade V of elementary school. The research employed a quasi-experimental method with a quantitative approach. The participants consisted of two classes from a public elementary school. Data were collected through learning achievement tests administered as pretests and posttests. Data analysis included the Shapiro–Wilk normality test, Levene’s homogeneity test, the Wilcoxon test, and effectiveness analysis using the N-Gain score. The results indicated a significant improvement in learning outcomes in the experimental class compared to the control class. The Wilcoxon test revealed a statistically significant difference between the pretest and posttest scores. Based on these findings, it can be concluded that the integration of AI is effective in supporting the learning of plane geometry in Grade V of elementary school. The implications of this study suggest that the use of AI in mathematics learning, particularly in plane geometry, can serve as an innovative and effective instructional strategy to enhance students’ conceptual understanding.